Lipophilic but not hydrophilic statin therapy improves cardiodynamics without affecting skeletal muscle morphology or function in geriatric Wistar rats - Irena A. Rebalka; Razan Alshamali; Tiffany L. vanLieshout; Molly A. Gingrich; Matthew R. Marlatt; Vladimir Ljubicic; Jeremy A. Simpson; Thomas J. Hawke (PLoS ONE, 2026)
While older adults are the most prominent human cohort currently necessitating or receiving cholesterol-lowering statin therapy, most preclinical testing of the efficacy and side effects that accompany statin use are conducted on juvenile adult rodents. Furthermore, varying pharmacodynamics between hydrophilic and lipophilic statins may lead to different therapeutic outcomes. The purpose of this study was to compare the efficacy, specifically modifications to cardiovascular parameters, and safety, namely presence or absence of a pathological skeletal muscle phenotype, of hydrophilic rosuvastatin (RSV) versus lipophilic atorvastatin (ATV) therapy in a geriatric rodent model. Briefly, 25- to 27-month-old Wistar rats were provided control, RSV, or ATV treatment for 30 days. Cardiac hemodynamics, muscle functional testing, open-field behaviours, and skeletal muscle morphology were evaluated. Whole-heart weight was lower in ATV-treated than in RSV-treated animals. Heart rate, rate of left ventricle pressure change, and arterial pressure were lowered by ATV but not RSV. These results are hypothesized to suggest attenuation of age-related sympathetic overactivity with ATV treatment. No differences in muscle histology, function, or open-field testing behaviours were observed between groups, indicating the absence of an overt statin-associated skeletal muscle phenotype. Overall, in geriatric rodents that more appropriately mimic the age of humans that are prescribed statin therapy, lipophilic ATV, but not hydrophilic RSV, had positive effects on cardiac function without negatively impacting the skeletal muscle.